Elimination of typhoid: possibility or pipe dream? - Purcell, R; Pollard, AJ (Wiley, 2020)
The elimination of typhoid would have a substantial impact on the health of millions of people living in South and Southeast Asia and sub-Saharan Africa. Like many diseases before it, there are significant challenges to elimination, including access to safe drinking water and adequate sanitation practices, the availability of a vaccine, the identification and management of chronic carriers and the emergence of anti-microbial resistance. While provision of clean water and adequate sanitation must remain the ultimate goal, in the short term, required to cornerstone elimination in endemic areas, is an efficacious vaccine. Recent evidence of effectiveness with a tetanus-toxoid conjugate vaccine offers an opportunity for an immunogenic and safe vaccine able to be delivered to young children. Shown to be efficacious in Nepal, where infection is endemic, it may be a viable option in public health programmes moving towards elimination.